US–China health exchange and collaboration following COVID-19 - Li, Liming; Wang, Kean; Chen, Zhuo; Koplan, Jeffrey P (2021)
Strong US–China collaboration on health and medicine is a crucial element of the global effort against COVID-19. We review the history of health collaboration and exchanges between the public and private sectors in the USA and China, including the long-lasting collaboration between governmental public health agencies of the two countries. Academic and scientific exchanges should be reinvigorated and the increasing valuable role of non-profit foundations acknowledged. The shared interests of the two countries and the magnitude of the pandemic necessitate both countries to collaborate and cooperate. We provide recommendations to the two governments and the global health community to control the ongoing COVID-19 pandemic and prepare for future threats. Translation: For the Chinese translation of the abstract see Supplementary Materials section.